TV PROGRAM BOCAH PETUALANG, THE MOUNTAIN THEME AS A CREATORS ON THE CREATIVITY OF CHILDREN'S SDN PETERONGAN SEMARANG - solifah, puji (Universitas PGRI Semarang, 2020)
In this globalization era, the development of television has developed rapidly. This is proven by the number of various kinds of TV programs, including soap operas, comedy, cartoon films and children's films. But not all TV programs are good for the development of children's skills. There is one children's film that has a positive impact on student skills, that is Bocah Petualang, one of the TV programs on Trans7. This TV program shows some children who do their activities in the area and make handwork or skills that they often do to play. Their activities in the area are displayed attractively and full of cohesiveness. The researcher chose SDN Peterongan Semarang to measure the level of creativity of students in class V. The research in this thesis is a qualitative research. This type of research is phenomenological research in the Si Bolang Trans7 program. In this case the researchers used banana fronds to students so that they were able to develop their creativity. The primary data source in this study is the Bocah Adventurer TV program consisting of three episodes, namely the Babad Tanah Jawa episode and the Riang Gembira episode on Bumi Rancah, which were invited from Youtube, while the secondary data source was the result of an interview with the Principal, grade V teacher, grade students V and parents / guardians of students.Keywords: TV programs, adventurous children, creativity